Histopathology of congestive nephropathy: a case description and literature review - Husain-Syed, Faeq; Rangaswami, Janani; Núñez, Julio; Skrzypek, Susanne; Jux, Christian; Gröne, Hermann-Josef; Birk, Horst-Walter; Justus Liebig University Giessen (My University, 2024)
Congestive nephropathy is an underappreciated manifestation of cardiorenal syndrome and is characterized by a potentially reversible kidney dysfunction caused by a reduced renal venous outflow secondary to right-sided heart failure or intra-abdominal hypertension. To date, the histological diagnostic criteria for congestive nephropathy have not been defined. We herein report a case of acute renal dysfunction following cardiac allograft failure and present a review of the relevant literature to elucidate the current understanding of the disease. Our case demonstrated that congestion-driven nephropathy may be histopathologically characterized by markedly dilated veins and peritubular capillaries, focally accentuated low-grade acute tubular damage, small areas of interstitial fibrosis, and tubular atrophy on a background of normal glomeruli and predominantly normal tubular cell differentiation.
Keywords: ddc:610